2012
DOI: 10.1039/c2dt30866e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetico-mechanistic studies of cyclometalating C–H bond activation reactions on Pd(ii) and Rh(ii) centres: The importance of non-innocent acidic solvents in the process

Abstract: The activation of C-H bonds in homogeneous systems has been the subject of study for many years due to its involvement in important industrial catalytic processes. A large number of reviews on the different areas involved have appeared, but those dealing with kinetic studies, including activation parameters, are rather scarce due to the severe difficulties in interpreting experimental data. In this perspective, the information available from kinetico-mechanistic studies of cyclometalation reactions on Pd(II) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 130 publications
3
38
0
Order By: Relevance
“…We have already reported that the metalation of 1 d⋅ HCl– 1 f⋅ HCl ( p ‐OMe, p ‐Br and m ‐Br) affords the corresponding orthopalladated complexes 3 d – f with very similar reaction yields (60–66 % in 24 h), which are similar to the yield obtained for unsubstituted 1 a⋅ HCl in the same time (67 %) 8c. This results indicates that the CH bond activation step occurs in practically the same circumstances in these cases, and that the process is not tuned by changing the electronic nature of the aryl substituents, as found in other cyclopalladated systems 21b. An exception is 1 g⋅ HCl, which seems to give a higher yield of the palladated dinuclear complex 3 g ;8c the fact that this complex is not obtained in pure form, and that the yield can only be estimated by the further reactivity of the mixture containing 3 g , could be responsible for the differences reported.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…We have already reported that the metalation of 1 d⋅ HCl– 1 f⋅ HCl ( p ‐OMe, p ‐Br and m ‐Br) affords the corresponding orthopalladated complexes 3 d – f with very similar reaction yields (60–66 % in 24 h), which are similar to the yield obtained for unsubstituted 1 a⋅ HCl in the same time (67 %) 8c. This results indicates that the CH bond activation step occurs in practically the same circumstances in these cases, and that the process is not tuned by changing the electronic nature of the aryl substituents, as found in other cyclopalladated systems 21b. An exception is 1 g⋅ HCl, which seems to give a higher yield of the palladated dinuclear complex 3 g ;8c the fact that this complex is not obtained in pure form, and that the yield can only be estimated by the further reactivity of the mixture containing 3 g , could be responsible for the differences reported.…”
Section: Resultssupporting
confidence: 79%
“…For the fully unsubstituted amino ester ligand 1 a , the data collected are consistent with the expected highly ordered and entropy‐demanding transition state, which is accompanied by an important volume contraction 13a. 21a,b In this respect, it is noticeable that no significant differences in the activation parameters are observed for the reactions carried out in acetone or toluene solution, which is indicative of the innocent and nonparticipative nature of these solvents in the process. These differences (or similarities), have already been established as very significant for other organometallic systems of diverse nature 28.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…[1] Many studies of the reactivity and characterization of organometallic complexes including C-X (X = halide) bond activation have been performed and related kinetic studies have also been conducted in several cases. [8] In the work reported here, oxidative addition reactions of organoplatinum(II) complexes [PtMe 2 (NN)] (NN = bpy or phen) with PhCH 2 CH 2 Br were carried out to synthesize new organoplatinum(IV) complexes. The reactivity of PhCH 2 CH 2 Br in its oxidative addition reactions was theoretically investigated and compared to that of CH 3 CH 2 Br and PhCH 2 Br.…”
Section: Introductionmentioning
confidence: 99%